MICROSPHERULES IN MODERN BEACH SEDIMENTS OF THE NORTH-WESTERN PART OF THE BLACK SEA - V.A. Nesterovskyi; M.A. Deiak; N.O. Hryshchanko (Геологія і корисні копалини Світового океану)
The article presents the results of studies of microspherules from beach sediments of the north-western part of the Black Sea. Microspherules are common in fractions less than 0.5 mm, have a spherical shape and a different chemical composition. They are mainly ferrous, magnesium-calcium-manganese, silicate and polycomponent. According to the authors, microspherules are of technogenic origin.